An Efficacy and Safety Study of Remogliflozin in Obese Indian Type 2 Diabetes Mellitus Patients Who Were Inadequately Controlled on Insulin Glargine Plus other Oral Hypoglycemic Agents - Shankar, Anand (Current Diabetes Reviews, 2021)
Aims & Objectives: The objective of this retrospective study was to investigate the efficacy of adding remogliflozin to current insulin glargine plus two oral drug i.e. metformin and teneligliptin therapy in poorly controlled Indian type 2 diabetes. Materials and Methods: 173 study participants were initially selected from patient database who continued on their insulin glargine or received an increased dose of insulin glargine along with other OHA based therapy (Group A) and 187 were selected who had received remogliflozin (100 mg BD) (Group B) in addition to insulin glargine along with other OHA based therapy. Glycated haemoglobin (HbA1c), total daily insulin dose, body weight, and the number of hypoglycemic events were recorded at weeks 0, 12 and 24. Results: During the study, mean values of HbA1c, FBG and P2BG were significantly reduced in both groups. Insulin requirements decreased from 45.8 ± 16.7 IU/day to 38.5 ± 13.5 IU/day at week 12 (P < 0.001) and at week 24 even further decreased to 29.5 ± 14.5 IU/Day. Twenty three patients in group B were able to cease insulin treatment altogether after 24 week treatment. It has been observed that to attain tight blood glucose control, we need to increase insulin dose in group A from 45.5 ± 16.5 IU/Day to 51.5 ± 14.5 at week 12 (P<0.01), which further increased to 53.8 ± 12.8 IU/Day at week 24 (P<0.01). Adding remogliflozin showed significant effect on blood pressure (P < 0.001) and weight reduction (P < 0.001). It has been observed that 38% patients achieved targeted HbA1c (≤7%) in group B where it was 22% in group A. Conclusion: Results demonstrate that in uncontrolled T2DM patients, remogliflozin 100 mg BD can successfully lay a foundation for prolonged good glycemic control. Early addition of remogliflozin with insulin glargine plus OHAs may be an alternative compared to intensive up titration of insulin daily dose in people with uncontrolled T2DM.
Keywords: metformin